Normal Gaze Cueing in Children with Autism Is Disrupted by Simultaneous Speech Utterances in "Live" Face-to-Face Interactions. (18th October 2011) - Potter, Douglas D.; Webster, Simon
Abstract : Gaze cueing was assessed in children with autism and in typically developing children, using a computer-controlled "live" face-to-face procedure. Sensitivity to gaze direction was assessed using a Posner cuing paradigm. Both static and dynamic directional gaze cues were used. Consistent with many previous studies, using photographic and cartoon faces, gaze cueing was present in children with autism and was not developmentally delayed. However, in the same children, gaze cueing was abolished when a mouth movement occurred at the same time as the gaze cue. In contrast, typical children were able to use gaze cues in all conditions. The findings indicate that gaze cueing develops successfully in some children with autism but that their attention is disrupted by speech utterances. Their ability to learn to read nonverbal emotional and intentional signals provided by the eyes may therefore be significantly impaired. This may indicate a problem with cross-modal attention control or an abnormal sensitivity to peripheral motion in general or the mouth region in particular.